The new north american classification of Mental Disorders – DSM - 5 (Brazilian Journal of Behavioral and Cognitive Therapy, 2014)
Some of the main changes introduced in the new North American diagnostic classification are presented in a synthetic way to the behaviour analysis community. Result of field studies that investigated the validity of previous diagnoses has advantages, but gaps in the present knowledge of mental disorders are still there. Some of the main criticisms are also presented.
Keywords: Diagnostic Classification; Psychiatry; Mental Disorders; DSM-5